2019
DOI: 10.1002/bjs.11101
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of clinical trials examining the benefit of structured home exercise in patients with peripheral artery disease

Abstract: Background: Supervised exercise is recommended for the management of peripheral artery disease (PAD); however, the uptake is limited. Structured home exercise programmes may be more feasible, but their effectiveness is unclear. This systematic review and meta-analysis examined the benefit of structured home exercise programmes for treating PAD in comparison to controls not receiving an exercise programme.Methods: A literature search was conducted to identify RCTs comparing structured home exercise with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 36 publications
2
58
0
1
Order By: Relevance
“…The first aim of the present study was to identify which exercise regime was effective in improving voluntary exercise capacity in our LEAD mouse model. In agreement with human studies 13,14 , we found that running was the most effective. Indeed, forced and voluntary running exercise were equally effective in improving 24-TRD, in spite of their differences: while the activity pattern of the running wheel is characterized by several short bouts (~ 150 s each) of high-speed running, separated by short breaks (~ 30 s), treadmill running forces the animal to run for a sustained period at moderate speed 15 .…”
Section: Discussionsupporting
confidence: 90%
“…The first aim of the present study was to identify which exercise regime was effective in improving voluntary exercise capacity in our LEAD mouse model. In agreement with human studies 13,14 , we found that running was the most effective. Indeed, forced and voluntary running exercise were equally effective in improving 24-TRD, in spite of their differences: while the activity pattern of the running wheel is characterized by several short bouts (~ 150 s each) of high-speed running, separated by short breaks (~ 30 s), treadmill running forces the animal to run for a sustained period at moderate speed 15 .…”
Section: Discussionsupporting
confidence: 90%
“…The increase in the majority of the walking performance outcomes suggest that the key to induce improvements is a well-structured exercise program, with isolated aerobic exercise or combined with resistance exercise, that complies with the specific PAD exercise doses. Accordingly, home-based exercise programs, if structured, involving adequate supervision and aimed to motivate the patients to increase physical activity levels or other behavioral interventions, can also improve walking performance outcomes (Golledge et al, 2019). The walking performance improvements are associated with significant enhancements in functional status, quality of life (Lauret et al, 2014;Novakovic et al, 2017), and also to considerable decreases in sedentary levels that may help in the management of cardiovascular risk factors (Morris et al, 2014;McDermott et al, 2016;Novakovic et al, 2017).…”
Section: Combined Exercise Vs Aerobic Exercisementioning
confidence: 99%
“…Supervised exercise programs have a higher efficacy in improving the physical fitness in particular the walking performance (i.e., claudication onset distance [COD], absolute claudication distance [ACD] or maximal walking distance [MWD]) and the symptomatology of this disease when compared to unsupervised exercise programs (McDermott et al, 2009;Mays and Regensteiner, 2013;McDermott, 2013). However, a recent meta-analysis found that structured home-based exercise programs are effective at improving walking performance in patients with PAD (Golledge et al, 2019). According to guidelines on the diagnosis and treatment of PAD by American Heart Association/American College of Cardiology (AHA/ACC) and European Society of Cardiology/European Society for Vascular Surgery (ESC/ESVS), patients should realize a supervised exercise walking program for a minimum of 30/45 min per session, performed at least 3 times per week for a minimum of 12 weeks (Gerhard-Herman et al, 2017;Aboyans et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis has also shown that home-based structured exercise therapy (HSET) -where patients perform the exercise at home but receive continuous feedback from healthcare personnel -may improve walking capacity 43 . The long-term effects of HSET still remain to be investigated.…”
Section: 2a Exercisementioning
confidence: 99%